Multidrug-resistant pulmonary tuberculosis in Esmeraldas, Ecuador (2018–2022): prevalence and clinical–epidemiological profile from a retrospective observational study - Jaime Angamarca-Iguago (Práctica Familiar Rural)
Background: Multidrug-resistant tuberculosis (MDR-TB) remains a growing public health concern globally, particularly in settings with limited diagnostic capacity and high disease burden. In Ecuador, Esmeraldas province has reported a disproportionately high number of TB cases. However, local evidence on resistance patterns and patient characteristics is scarce.